2014
DOI: 10.1302/2046-3758.310.2000304
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a model-based measurement of the minimum insert thickness of knee prostheses

Abstract: IntroductionWear of polyethylene inserts plays an important role in failure of total knee replacement and can be monitored in vivo by measuring the minimum joint space width in anteroposterior radiographs. The objective of this retrospective cross-sectional study was to compare the accuracy and precision of a new model-based method with the conventional method by analysing the difference between the minimum joint space width measurements and the actual thickness of retrieved polyethylene tibial inserts. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Radiostereometry (RSA) and recent developments of advanced model-based software allow for the measurement of in-vivo PE wear in the Oxford medial UKA with high accuracy (Van IJsseldijk et al. 2011, 2014).…”
mentioning
confidence: 99%
“…Radiostereometry (RSA) and recent developments of advanced model-based software allow for the measurement of in-vivo PE wear in the Oxford medial UKA with high accuracy (Van IJsseldijk et al. 2011, 2014).…”
mentioning
confidence: 99%
“…For the Oxford unicompartmental knee arthroplasty, Horsager et al described wear rates of 40 and 50 µm per year for the cemented and cementless versions, respectively, which is slightly lower than what we have seen in our cohort [ 32 ]. The aforementioned study was conducted using the radiostereometic analysis (RSA), which has been shown to produce accurate results in total knee replacement wear analysis [ 33 , 34 ]. However, no study comparing wear assessed by RSA and subsequently by the retrieval analysis has been conducted so far, to the best of our knowledge, and a certain error in measurement has to be accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Contact‐loss between the articulating surfaces was measured using the mJSW. The mJSW was calculated as the shortest distance between the surface of the femur CAD model perpendicular to the surface of the flat tibial CAD model, using a validated method …”
Section: Methodsmentioning
confidence: 99%